Sludge Formation Analysis in Hydraulic Oil of Load Haul Dumper 811MK V Machine Running at Elevated Temperatures for Bioenergy Applications. (24th June 2021) - Siddiqui, MohdAhteshamHussain; Pal, Sandeep K; Dewangan, Nagesh; Chattopadhyaya, Somnath; Sharma, Shubham; Nekoonam, Saeed; Issakhov, Alibek
Abstract : Hydraulic oil degrades expediently during operating at elevated temperatures, and due to oil degradation, malfunction of all hydraulic components starts that hampers the hydraulic functioning of the machine. An inefficient component of the hydraulic system converts useful energy into heat. Overheating starts when the rate of heat energy escaping from the system overcomes the rate of heat dissipation. Viscosity, total acidic number (TAN), rheology, and FTIR analyses were carried out on the oil samples collected chronically, and the reasons for degradation and sludge formation were evaluated; the results showed that thermal cracking resistance capacity of the oil was low due to the imbalance percentage of additives in the base oil. Sludge impaired the system efficiency and prejudicially creates repercussions on power consumption. Sludge can be recycled for biofuel and to avoid imbalance in the ecosystem. The test result is plotted in a 3D view graph using the MATLAB R 2019 software for a better explanation. Variation in the behaviour of the hydraulic fluid with respect to time, temperature, shear stress, and shear rate was studied, and the result is validated with correlation and regression analyses.